2000
DOI: 10.1016/s0022-5347(05)66916-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Bacillus Calmette-Guerin and Dimethyl Sulfoxide for Treatment of Classic and Nonulcer Interstitial Cystitis:: A Prospective, Randomized Double-Blind Study

Abstract: Intravesical BCG has been presented as a promising new option for treatment of interstitial cystitis. We failed to demonstrate benefit from this treatment. Dimethyl sulfoxide had no positive effect on maximal functional capacity but resulted in a significant reduction in pain and urinary frequency, although only in patients with classic interstitial cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…110 Two RCTs compared DMSO to Bacillus Calmette-Guerin (BCG), one favouring DMSO (30% response rate compared to 10% for BCG, p<0.05) 111 and one concluding no benefit with either regimen. 112 Finally, two other RCTs compared DMSO to chondroitin sulfate (CS), or to CS plus hyaluronic acid, with significantly better performances of CS groups over DMSO for both objective and subjective outcomes (14-53 % for DMSO against 73% for GAG, p<0.05). 113,114 Other observational studies have described use of DMSO in combination with corticoids, bicarbonate, or heparin.…”
Section: Dimethylsulfoxide (Dmso) (Recommended In Select Patients Grmentioning
confidence: 99%
“…110 Two RCTs compared DMSO to Bacillus Calmette-Guerin (BCG), one favouring DMSO (30% response rate compared to 10% for BCG, p<0.05) 111 and one concluding no benefit with either regimen. 112 Finally, two other RCTs compared DMSO to chondroitin sulfate (CS), or to CS plus hyaluronic acid, with significantly better performances of CS groups over DMSO for both objective and subjective outcomes (14-53 % for DMSO against 73% for GAG, p<0.05). 113,114 Other observational studies have described use of DMSO in combination with corticoids, bicarbonate, or heparin.…”
Section: Dimethylsulfoxide (Dmso) (Recommended In Select Patients Grmentioning
confidence: 99%
“…In one trial, BoNTA showed a significant treatment effect on pain, urinary frequency, and urgency compared with BCG, but these findings require further research for confirmation [45]. The mechanism of BCG in IC/PBS treatment remains unclear though it may be related to local immune system impairment [28]. As shown above, BCG significantly improved GRA and urinary urgency in IC/PBS patients.…”
Section: Discussionmentioning
confidence: 92%
“…1). After a full-text review, the reasons for excluding reports were non-RCTs [4,26], other intervention interference [27,28], other similar diseases [9,29,30], and lack of desired outcome assessment [31]. The general characteristics of the studies included are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in two other RCTs, the group receiving intravesical BCG had no or marginal improvement (82,84). Oxybutynin, which has an anti-cholinergic effect reducing bladder spasm, was shown to significantly increase bladder capacity and was correlated with reduced frequency and improved quality of life (85).…”
Section: Intravesical Therapiesmentioning
confidence: 99%
“…The mechanism of action includes inhibition of mast cell activation with analgesic and inflammatory effects. Two rather small RCTs support its beneficial effect (81,82). However, the side effects of DMSO (garlic-like smell, taste) makes it almost impossible to perform a real placebocontrolled RCT.…”
Section: Intravesical Therapiesmentioning
confidence: 99%